The Interplay Between Lymphatic Vessels and Chemokines - Farnsworth, Rae H.; Karnezis, Tara; Maciburko, Simon J.; Mueller, Scott N.; Stacker, Steven A. (Frontiers in Immunology, 2019)
Chemokines are a family of small protein cytokines that act as chemoattractants to migrating cells, in particular those of the immune system. They are categorised functionally as either homeostatic, constitutively produced by tissues for basal levels of cell migration, or inflammatory, where they are generated in association with a pathological inflammatory response. While the extravasation of leukocytes via blood vessels is a key step in cells entering the tissues, the lymphatic vessels also serve as a conduit for cells that are recruited and localised through chemoattractant gradients. Furthermore, the growth and remodelling of lymphatic vessels in pathologies is influenced by chemokines and their receptors expressed by lymphatic endothelial cells in and around the pathological tissue. In this review we summarise the diverse role played by specific chemokines and their receptors in shaping the interaction of lymphatic vessels, immune cells and other pathological cell types in physiology and disease.